Therapeutic regulation of autophagy in hepatic metabolism - Katherine Byrnes; Sophia Blessinger; Niani Tiaye Bailey; Russell Scaife; Gang Liu; Bilon Khambu (Elsevier, 2022)
Metabolic homeostasis requires dynamic catabolic and anabolic processes. Autophagy, an intracellular lysosomal degradative pathway, can rewire cellular metabolism linking catabolic to anabolic processes and thus sustain homeostasis. This is especially relevant in the liver, a key metabolic organ that governs body energy metabolism. Autophagy's role in hepatic energy regulation has just begun to emerge and autophagy seems to have a much broader impact than what has been appreciated in the field. Though classically known for selective or bulk degradation of cellular components or energy-dense macromolecules, emerging evidence indicates autophagy selectively regulates various signaling proteins to directly impact the expression levels of metabolic enzymes or their upstream regulators. Hence, we review three specific mechanisms by which autophagy can regulate metabolism: A) nutrient regeneration, B) quality control of organelles, and C) signaling protein regulation. The plasticity of the autophagic function is unraveling a new therapeutic approach. Thus, we will also discuss the potential translation of promising preclinical data on autophagy modulation into therapeutic strategies that can be used in the clinic to treat common metabolic disorders.